ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO KEUANGAN (STUDI PADA PT. INDOSAT TBK DAN PT. XL AXIATA TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marli -; Ari Sulistyani; Dwi Danesty Deccasari (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
The company's financial ratios to measure financial performance through ratio analysis which aims to determine the comparisons consisting of: liquidity ratio, Current Ratiio, Quiick Ratio, Cash Ratio, solvency ratio, Total Debt to Total Asset, Total Debt to Equiity Ratio, Net Margin profitability ratio, Return Of Investment , Return On Equity and activity ratio (Inventory Turn Over, Fixed Asset Turn Over, Total Asset Turn Over. Quantitative method using descriptive is the type of research used in this research, namely by analyzing data in the form of numbers by calculating the company's financial statements. Objects at PT. Indosat Tbk and PT. XL Axiata Tbk in 2015-2018. The data used are secondary data taken from trusted sources, namely www.idx.co.id The data collection technique used is documentation techniques, the research was conducted through the official website of the Stock Exchange. Indonesia (BEI) 2015-2018. The analysis results from the measurement of financial ratios from the two companies from the analysis of the liquidity and solvency ratios of PT. XL Axiata is more liquid. From the analysis of profitability ratios and performance activity ratios of PT, Indosat Tbk is better than PT. XL Axiata Tbk.